Triple bands Class-C voltage-controlled power oscillator based on high-quality factor asymmetry inductor. (October 2021) - Mansour, Marwa; Mansour, Islam
Abstract: This work presents a complementary P–N class-C voltage-controlled power oscillator based on a new structure asymmetry inductor using a 130 nm CMOS process. The proposed asymmetry inductor is designed with different widths and various spaces between turns. This improves the quality factor (Q-factor) by 30.8% compared to the conventional inductor and also, shifts up self-resonance frequency (SRF) from 4.8 GHz to 7.8 GHz. In turns, the proposed inductor causes a 2 dB improvement in the phase noise of the oscillator. By using a single switching voltage the proposed voltage-controlled oscillator works in triple bands with a tuning range of 34.5% from 2 to 2.9 GHz, and low phase noise of −122 dBc/Hz @ 1-MHz offset frequency from 2.2 GHz carrier. The proposed VCO is class-C and draws 0.183 mA from 1 V supply voltage. The minimum achieved Figure-of-Merit (FOM) equals −195.5 dBc/Hz and the maximum given output power is 7 dBm. The active area of the proposed VCO equals 0.17 m m 2, while the total chip area including RF pads and output buffers is 0.56 m m 2 .